A Matrix Iterative Approach to Systematically Generate Hilbert-type Space-filling Curves - Ye, Ruisong; Liu, Li (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Hilbert-type space-filling curve has attracted much interest thanks to its mathematical importance and extensiveÂ applications in signal processing. In this paper, we construct the complete six Hilbert-type space-filling curves form a matrix point of view. The address matrix for each considered Hilbert-type space-filling curve can be easily generated by aÂ recursive manner. Besides the six Hilbert-type space-filling curves, we also construct their corresponding variationÂ versions. The merit of the matrix approach is that the iterative algorithm is easy to implement and can be generalized toÂ produce any other Hilbert-type space-filling curves and their variation versions.